Code in transition? The evolution of code of the street adherence in adolescence - Erickson, Jacob H. (Deviant behavior, 2020)
Using four waves (n = 2,385) from a student sample drawn in large U.S. cities, we examine the code of the streets’ influence on criminal offending and conflict management. Key to the analysis is the theoretical notion that effects are most pronounced for those who believe in the code intractably. We perform Latent Class Analysis to identify adherence types and use Latent Transition Analysis to measure the individual change in street-code class membership. Findings reveal four classes, distinguished mainly by the level of agreement. Those high and stable on the code are more likely to engage in crime and have diminished conflict management skills.